UNHEARD VOICES OF WOMEN IN THE BIBLE, WITH IMPLICATIONS OF EMPOWERMENT IN THE CONTEXT OF TODAY’S CHURCH - L.M. Mudimeli; J.D.N. Van der Westhuizen (Acta Theologica)
This article analyses the current status of women in the church and compares this with the status of women in the Bible. The unheard voices of women in the Bible have a corrective impact on the way in which women currently deal with their social ills. This article journeys with a narrative from the New Testament that encourages deconstruction of discourses that are harmful to women and reconstruction of healthy discourses that are inclusive and do not discriminate against women on the basis of gender. As the empowerment of women is located within the discourses of gender equality, a gender lens, which is a biblical liberation hermeneutic of vhusadzi theology, is employed to reconstruct positive discourses regarding people’s perceptions about women in societies. The researchers argue that the unheard voices of women are still an issue and that the empowerment of women still needs to be prioritised. The church can play a significant role in contributing towards the empowerment of women.